Linguistic construction of the expression 'Penantian' in Didi Kempot's lyrics: A semantic pragmatic analysis - Iswatiningsih, Daroe; Mujianto, Gigit; Artanti, Yeni (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2025)
This study explores the linguistic construction of the expressive speech act of penantian (waiting) in Didi Kempot's song lyrics by employing a descriptive qualitative method with a pragmatic-semantic framework, drawing from Searle’s theory of speech acts and Cruse’s lexical semantics. The analysis was conducted on a corpus of six popular songs selected purposively based on the dominance of penantian themes. Each lyric was examined in terms of its expressive act, contextual meaning, and cultural-symbolic references. This phenomenon of penantian, often associated with deep emotions such as sadness, longing, and resignation, reflects Didi Kempot’s strong identity as Indonesia’s “Godfather of Broken Heart.” The findings reveal eleven expressive variants of penantian (e.g., hope, longing, grief) and seven context-based meanings (e.g., longing for reunion, emotional endurance, betrayal of promises). Furthermore, linguistic representations are constructed through culturally loaded temporal (e.g.,